Sustainability determinants of cultural and creative industries in peripheral areas - Francesca Imperiale; Roberta Fasiello; Stefano Adamo (Journal of Risk and Financial Management, 2021)
Cultural and Creative Industries (CCIs) are increasingly recognized as part of the global economy and of growing importance for sustainable local development. However, the exploitation of their full potential depends on several issues concerning their entrepreneurial dimension and the context where they operate. The paper deals with these issues having the scope to investigate the main determinants of CCIs' sustainability in peripheral areas, to understand what kind of policy could better support the survival of CCIs and development in these areas, according to an end-user perspective. The research is part of an Interreg Greece-Italy project carried out from mid-2018 until the end of 2020 with specific reference to CCIs in Apulia (IT) and Western Greece (EL). A two-step mixed methodology has been used to figure out regional specializations and the specific aspects of the entrepreneurial structure and business sustainability in the cultural and creative sector (CCs). In the end, the paper shows and discusses the main determinants considered crucial for CCI sustainability, suggesting guidelines for local authorities supporting their economic development.
Keywords: 330; sustainability; cultural and creative industries; peripheral areas